Origin and taxonomic status of the Palearctic population of the stem borer Sesamia nonagrioides (Lefèbvre) (Lepidoptera: Noctuidae) - (:unkn) unknown (My University, 2011)
The major pest of maize in Mediterranean Europe, the stem borer Sesamia nonagrioides (Lefèbvre) (Lepidoptera: Noctuidae), has a fragmented distribution, north and south of the Sahara. The present study aimed: (1) to clarify the uncertain taxonomic status of the Palearctic and sub-Saharan populations which were first considered as different species and later on as subspecies (Sesamia nonagrioides nonagrioides and Sesamia nonagrioides botanephaga) and (2) to investigate the origin of the Palearctic population which extends from Spain to Iran, outside what is considered typical for this mainly tropical genus. We reconstructed the evolutionary history of both populations using one nuclear and two mitochondrial genes. The sub-Saharan taxon was fragmented in two isolated populations (West and East) whose mitochondrial genes were distant by 2.3%. The Palearctic population was included in the East African clade and its genes were close or identical to those of a population from Central Ethiopia, where the species was discovered for the first time. Similarly, in Africa, the alleles of the nuclear gene were distributed mainly in two West and East clades, whereas some Palearctic alleles belonged to the West clade. The Palearctic population originated therefore from East and West Africa and is the progeny of the cross between these two African populations. The main species concepts were in agreement, leading to the conclusion that the three populations are still conspecific. In the surveyed regions, the species therefore does not include two subspecies but three isolated populations. The Palearctic population suffered from severe bottlenecks that resulted in the fixation of one East African mitochondrial genome and the large reduction in its genetic diversity compared to the African populations. The data suggest that natural colonization of the Palearctic region was more plausible than human introduction. The allelic distribution of the Palearctic population was
Keywords: African Research